Possessive Expressions in Javanese - Kamilatun Baroroh; Mulyadi, Mulyadi (Talenta Publisher, 2020)
This study aims to describe the characteristics of Possessive Construction in Javanese and relations of expressions between Possessor (PR) and Possessum (PS). The source of data are texts in Javanese from Djaka Lodang Magazine Volume XXII, XXIV, XXIX year 2017 and Panjebar Semangat Magazine Volume 29, 19, and 20 from May until July 2018 which contains Possessive Constructions in Javanese also informant who is a native speaker of Javanese. The data are analyzed using Simak Method, with base Sadap technic and advance Simak-Bebas libat cakap technic and Catat technic, meanwhile technic for analyzing the data used are Agih Method to determine the Possessive Construction dan Padan Method to determine the relation between PR and PM elements. Javanese Possessive Constructions marked with clitics -e or Â-ne as possessive marker. The results show Javanese Possessive Constructions meaning exists at polymorphemic level, phrase level, and clause level. On polymorphemic level, possessive meaning expressed by nouns followed by enclitics persona pronoun. On Phrase level, possessive meaning expressed by noun which followed by noun persona and noun followed by noun. Persona pronoun acts as PR. Noun which acts as PR are (Ilahi), animal, plants and (concrete) noun. On clause level possessive meaning expressed by verb which occupy predicate (P). Noun occupying subject in clause recognized as possession (PM). In Javanese, it is found Possessive Construction which sates the relationship of proprietary in the form of; Possessive Construction in which PM elements is non-humane noun and PR elements is humane noun or persona pronoun, PM element is humane noun and PR element is humane (self-name) or persona pronoun, and PM element is non-living noun and PR element also non-living noun.